Global Cybersecurity: New Directions in Theory and Methods - Stevens, Tim (2018)
This thematic issue advocates a range of novel theoretical and methodological directions applicable to cybersecurity studies. Drawing on critical International Relations theory, Science and Technology Studies, participant observation, quantitative political science, and other social science methods and theory, the contributors advance modes of invigorating the exploration of cybersecurity as an assemblage of sociotechnical practices. In so doing, this issue seeks to enhance understanding of the politics and strategies of cybersecurity, one of the most complex and diverse technical and political challenges of our contemporary world.